Glycerol purification using reactivated spent bleaching earth from palm oil refineries: Zero-waste approach. Issue 3 (June 2021) - Yuliana, Maria; Trisna, Luciana; Sari, Feprita; Lunardi, Valentino Bervia
Abstract: This work uses reactivated spent bleaching earth (RSE) from palm oil refineries to reduce the impurities content (e.g., free fatty acid (FFA), carotenoid and chlorophyll) in crude glycerol. The influences of three important reactivation parameters on the removal of impurities are studied. The maximum removal percentage of all impurities is obtained using the RSE fabricated at activation temperature T  = 40 °C, n-hexane to spent earth ratio m h = 15, and surfactant loading m c = 0.75 wt%; which, hereinafter referred to as RSE-m. Further glycerol purification test using RSE-m at various adsorption temperature ( T a ) and RSE-m loading ( m a ) show that FFA, carotenoid, and chlorophyll are effectively reduced by 47.45, 93.39, and 96.63 wt%, respectively, at T a = 50 °C and m a = 10 wt%., with all specification comparable, if not superior, to those of commercial industrial grade glycerol. The kinetic, isotherm and thermodynamic studies also suggest that the adsorption of the pigmented compounds on the RSE-m surface is spontaneous, endothermic, and driven by physical attraction via hydrophobic binding (for both pigments) and electrostatic interaction (for chlorophyll only). The adsorption results indicate that RSE-m has a great affinity to all glycerol impurities, and can be considered as a promising adsorbent for glycerol purification. As this study implements the zero-waste approach by using RSE, it will prominently reduce the solid waste generated by the palm oil refineries, and at the same time, offers a cost-effective route for the refining of glycerol. Graphical Abstract: ga1 Highlights: A waste-based bleaching agent for glycerol purification, RSE-m, is synthesized. RSE-m has been successfully applied to remove three major impurities from glycerol. RSE-m shows a high affinity towards carotenoids and chlorophyll (>90% removal rate). The adsorption of pigments on RSE-m is driven by physical hydrophobic binding.